Philosophical Identities in Market for University Education - Denis, Sekiwu; Nicholas, Itaaga; Anthony Mugagga, Muwagga (Makerere Journal of higher education, 2020)
The study examines the metaphysics and political philosophy behind market competition for Uganda's University Education. using grounded theory to filter the voices of 12 participants, the first phase of study, which was qualitative, revealed that a rival (contestable) market of University education in Uganda.